Incidence and impact of hospital-acquired pneumonia: a Portuguese nationwide 4-Year study - Gonçalves-Pereira, J (2021)
We present the incidence of hospital-acquired pneumonia (HAP) in Portugal during a 4-year period (2014-2017). Data were retrieved from the 100 Portuguese Hospital diagnosis discharge database for adult patients and included gender, age, chronic comorbidities, mortality and hospital length of stay. We found 28,632 episodes of HAP, an incidence of 0.95 per 100 admissions. HAP patients had both a prolonged hospital length of stay (mean 26.4 days) and high mortality (33.6%). Most episodes occurred in patients aged ≥65 years and in males (76.1% and 61.7%, respectively). Invasive ventilation was required in 18.8%.